Binding to serine 65‐phosphorylated ubiquitin primes Parkin for optimal PINK1‐dependent phosphorylation and activation. (26th June 2015) - Kazlauskaite, Agne; Martínez‐Torres, R Julio; Wilkie, Scott; Kumar, Atul; Peltier, Julien; Gonzalez, Alba; Johnson, Clare; Zhang, Jinwei; Hope, Anthony G; Peggie, Mark; Trost, Matthias; van Aalten, Daan MF; et al.
Abstract Mutations in the mitochondrial protein kinase PINK1 are associated with autosomal recessive Parkinson disease (PD). We and other groups have reported that PINK1 activates Parkin E3 ligase activity both directly via phosphorylation of Parkin serine 65 (Ser65)—which lies within its ubiquitin‐like domain (Ubl)—and indirectly through phosphorylation of ubiquitin at Ser65. How Ser65‐phosphorylated ubiquitin (ubiquitinPhospho‐Ser65) contributes to Parkin activation is currently unknown. Here, we demonstrate that ubiquitinPhospho‐Ser65 binding to Parkin dramatically increases the rate and stoichiometry of Parkin phosphorylation at Ser65 by PINK1 in vitro. Analysis of the Parkin structure, corroborated by site‐directed mutagenesis, shows that the conserved His302 and Lys151 residues play a critical role in binding of ubiquitinPhospho‐Ser65, thereby promoting Parkin Ser65 phosphorylation and activation of its E3 ligase activity in vitro. Mutation of His302 markedly inhibits Parkin Ser65 phosphorylation at the mitochondria, which is associated with a marked reduction in its E3 ligase activity following mitochondrial depolarisation. We show that the binding of ubiquitinPhospho‐Ser65 to Parkin disrupts the interaction between the Ubl domain and C‐terminal region, thereby increasing the accessibility of Parkin Ser65. Finally, purified Parkin maximally phosphorylated at Ser65in vitro cannot be further activated by the addition of ubiquitinPhospho‐Ser65. Our results thus suggest that a major role of ubiquitinPhospho‐Ser65 is to promote PINK1‐mediated phosphorylation of Parkin at Ser65, leading to maximal activation of Parkin E3 ligase activity. His302 and Lys151 are likely to line a phospho‐Ser65‐binding pocket on the surface of Parkin that is critical for the ubiquitinPhospho‐Ser65 interaction. This study provides new mechanistic insights into Parkin activation by ubiquitinPhospho‐Ser65, which could aid in the development of Parkin activators that mimic the effect of ubiquitinPhospho‐Ser65.